POTENSI ANTIOKSIDAN KULIT BATANG TUMBUHAN KETAPANG (Terminalia catappa Linn.) - Siti Fauziah; Syahmani Syahmani (Universitas Lambung Mangkurat, 2011)
Abstrak: Three phenolic compound, hidroxybenzoat acids (gallat acids), kamferol, and 3,7,4’-trihidroxyflavonol, had been isolated from ethanol extracts of tree bark of Terminalia catappa Linn with soxhletation method, TLC method use BAA, Phenol, BEA solvent. The structures of these compounds were are established base on spectroscopic UV spectra, as well as by comparation with those reported data. Antioxidan total effect (DNPH method) of the isolated compounds showed activities with IC50 776,58 ppm, hydrogen peroxide scavenging scavenging (Ruch method) showed 387,6 ppm better than stantard antioxidan (vitamin E, tocopherol).Key words: Terminalia catapa Linn, phenolic compound, antioxidan